Improvement Of Knowledge and Skills of Hospitality in Tourism Group in Budo Village, District Wori, North Sulawesi Province - Benny Irwan Towoliu; Bernadain Dainty Polii; Jufrina Mandulangi (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
A hospitality attitude is needed by the local community when the village where they live will become as a tourism village. This attitude is closely related to the way the community welcomes guests who come and even stay overnight in tourist villages. The aim of this training program is to improve hospitality knowledge and skills in tourism groups in Budo Village, wori sub-district, North Minahasa Regency. The training method is carried out in the form of: a teaching system, simulation through role play, and at the end of the training an evaluation of the entire material being taught is carried out. The expected outcome is an increase in the knowledge and skills of the tour groups and has a broad impact on the local community in Budo Village